Perubahan Organisasi Bagi Pengelola Madrasah Dalam Menghadapi Persaingan Global - Nurhadi, Ali (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
Changing is as global phenomenon that can not be dammed. Organizational change is as transition from its current state to some desired state. Madrasah is an organization that needs to be maintained and even developed, because the quantity it’s large enough so that, it will be able to contribute the development of education. Globalization Era has been arriving and offering intense competition including for the existence of Madrasah. Therefore, the organizer of madrasah must begin to improve organizational change in order to face the competition in this Globalization Era.Organizational change can be influenced by internal or external factors. Therefore, the strategy must be prepared. The strategies used are adjusted to the conditions of each madrasah, because the existing of madrasah has different positions both in quantity, quality of human resources, and other supporting components, The formulation of the strategy can be preceded by the formulation of the vision and mission of the organization based on SWOT analysis (Strenghts Weakness Opportunities Threats), followedby the determination of specific objectives and organizational strategies to achieve the vision and misssion.